The Inhibition and Communication Approaches of Local Languages Learning Among Millennials - Hidayat, Dasrun; Rahmasari, Gartika; Wibawa, Darajat (International Journal of Language Education, 2021)
Local languages which are also referred as mother tongue should be attached to every child as individual. The re-orientation of language due to global influences should not mean forgetting the local language. Globalization and traditions can run simultaneously so that millennial generations are not only proficient in foreign languages, but also understand in using their local languages. This is a communication and culture research. The purpose of this study was to determine the millennials assumptions about local languages and the teaching approaches needed. An integrated teaching approach is needed so that it can restore the millennials’ interest and confidence in speaking their local languages. This research used a descriptive qualitative method with interview techniques, involving millennial generation from Jakarta, West Java and Lampung Provinces. The results of the study show that some of the millennials can speak their local languages but not as active speakers. There are two major obstacles that prevent the millennials to speak their local languages, namely internal and external factors. Internal factor that prevents them from speaking their local languages is family, and the external factors include peers, environment and technology. To encourage the use of local language, the government has issued Regional Regulations (PERDA) so that local languages can be used by daily life such as in schools. In addition, equality communication model can be used in teaching local languages, that include seriousness, openness, acceptance, and flexible teaching This approach is supported by binding local government regulations that require the use of local languages in a variety of contexts, including the language of instruction in education.